2018
DOI: 10.3390/nu10050574
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of a Special Acidified Milk Protein Drink with Cognitive Performance: A Randomized, Double-Blind, Placebo-Controlled, Crossover Study in Healthy Young Adults

Abstract: A previous in vivo study with rats suggested that a special milk protein drink manufactured using an acidification procedure to suppress the aggregation of milk proteins was absorbed quickly after feeding. We performed a randomized, double-blind, placebo-controlled, repeated-measure crossover study to investigate the short-term effects on cognitive performance in 29 healthy young adult men after they consumed this drink in the morning. After an overnight fast, subjects were tested for performance in the Uchida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Participants were given a 10-s resting period before each task periods. Kraepelin and 2-back are relatively easy cognitive tasks and used repeatedly in one day of the examination without leaning effects [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants were given a 10-s resting period before each task periods. Kraepelin and 2-back are relatively easy cognitive tasks and used repeatedly in one day of the examination without leaning effects [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Increased performance in the plasmalogen group was more notable in the middle (5 and 6 min) and toward the end of the 10-min task ( Figure 3 ). To our knowledge, none of the previous intervention studies have addressed the effect on the minute-specific performance in the Uchida-Kraepelin test ( Ataka et al, 2008 ; Johnson et al, 2016 ; Takanari et al, 2016 ; Saito et al, 2018 ). It could be argued that plasmalogens may maintain the performance in the middle of work, elicit the so-called last spurt in work performance, and increase mental concentration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sympathetic nervous system was in a dominant state in these individuals, with a high LF/HF ratio, which is an indicator of the autonomic nervous system balance, exceeding the normal value of 2.0. Previous studies have shown that Uchida-Kraepelin stress affects heart rate variability [31][32][33][34]. We selected subjects who felt that taking the Uchida-Kraepelin test was stressful had a substantial increase in their LF/HF ratios.…”
Section: Discussionmentioning
confidence: 99%